Detection of infectious bronchitis virus 793B, avian metapneumovirus, Mycoplasma gallisepticum and Mycoplasma synoviae in poultry in Ethiopia - Hutton, S.; Bettridge, Judy M.; Christley, Robert M.; Habte, T.; Ganapathy, K. (Springer, 2017)
A survey was conducted into respiratory infectious diseases of poultry on a chicken breeder farm run by the Ethiopian Institute of Agricultural Research (EIAR), located in Debre Zeit, Ethiopia. Oropharyngeal swabs were collected from 117 randomly selected birds, and blood was taken from a subset of 73 of these birds. A combination of serological and molecular methods was used for detection of pathogens. For the first time in Ethiopia, we report the detection of variant infectious bronchitis virus (793B genotype), avian metapneumovirus subtype B and Mycoplasma synoviae in poultry. Mycoplasma gallisepticum was also found to be present; however, infectious laryngotracheitis virus was not detected by PCR. Newcastle disease virus (NDV) was not detected by PCR, but variable levels of anti-NDV HI antibody titres shows possible exposure to virulent strains or poor vaccine take, or both. For the burgeoning-intensive industry in Ethiopia, this study highlights several circulating infectious respiratory pathogens that can impact on poultry welfare and productivity.